Studi Kasus Motivasi Belajar Siswa sebagai Anak Buruh Migran di SMP Negeri 1 Bandung Tulungagung - IM Hambali; Yuliati Hotifah; IM Hambali; Reiska Yunita Dewi; Reiska Yunita Dewi (Universitas Negeri Malang, 2021)
Abstract: This study aims to increase knowledge about the influence of parents 'presence when children learn and learning motivation of migrant workers' children at SMP Negeri 1 Bandung, Tulungagung. The type of research used is a case study, through interviews with snowball sampling techniques, which are likened to getting information continuously and will only stop when the data is saturated. In addition, the interview technique used by researchers is in-depth interviews. The research steps carried out were preceded by observation, the first observation conducted by the researcher examined the data of students who have parents as migrant workers. Researchers also conducted interviews with counseling teachers regarding the learning behavior of migrant workers' children in class and what problems usually bother the students of migrant workers in learning. Observations that the two researchers conducted were by way of frank observation entering the classroom and observing the learning and learning process in which there were students of migrant workers' children. The results of the observations show that the learning behavior of students of migrant workers' children is different from those of students who are not children of migrant workers. Therefore, the researcher decided to do a research to find out what motivates the students of migrant workers to learn. Data collection, the researcher chose 4 students who according to the researcher were included in the category as data sources. Researchers conducted interviews with 4 children of migrant workers with in-depth interviews. Furthermore, data analysis is carried out by means of data reduction, data display, and conclusion drawing / verification. Meanwhile, to test the validity of the data using the credibility test (internal validity). Abstrak: Penelitian ini bertujuan untuk menambah pengetahuan tentang pengaruh kehadiran orang tua saat anak belajar dan motivasi belajar siswa anak buruh migran di SMP Negeri 1 Bandung, Tulungagung. Jenis penelitian yang digunakan adalah studi kasus (case study), melalui wawancara dengan teknik sampling snowball yang diibaratkan mendapatkan informasi secara terus menerus dan baru akan berhenti saat data telah jenuh. Selain itu teknik wawancara yang digunakan peneliti adalah wawancara secara mendalam (in depth interview). Langkah penelitian yang dilakukan diawali dengan observasi, observasi yang pertama dilakukan peneliti memeriksa data siswa yang memiliki orang tua sebagai buruh migran. Peneliti juga melakukan wawancara kepada guru BK mengenai bagaimana perilaku belajar siswa anak buruh migran saat di kelas dan masalah apa saja yang biasa mengganggu siswa anak buruh migran dalam belajar. Observasi yang kedua peneliti lakukan dengan cara observasi terus terang ikut masuk kedalam kelas dan mengamati proses belajar dan pembelajaran yang didalamnya terdapat siswa anak buruh migran. Hasil dari observasi menunjukan perilaku belajar siswa anak buruh migran yang berbeda dengan siswa yang bukan anak buruh migran. Oleh karena itu peneliti memutuskan melakukan penelitian untuk mengetahui apa yang dapat menjadi motivasi belajar siswa anak buruh migran. Pengumpulan data, peneliti memilih 4 siswa yang menurut peneliti masuk dalam kategori sebagai sumber data. Peneliti melakukan wawancara kepada 4 siswa anak buruh migran dengan wawancara mendalam. Selanjutnya analisis data dilakukan dengan cara data reduction, data display, dan conclusion drawing/verification. Sedangkan untuk uji keabsahan data menggunakan Uji credibility (validitas internal).